ASRĀR AL-TAQDĪM WA AL-TA’KHĪR FĪ KALIMATAY AL-ẒULUMĀT WA AL-NŪR FĪ AL-QUR’ĀN AL-KARĪM: DIRĀSAH DALĀLAT AL-ALFĀZ AL-QUR’ĀNIYYAH - Agustono, Ihwan; Al Islam, Nizhamullah Muhammad (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
The terms al-Zulumat and al-Nur, which are both derived from the Qur'an, are discussed in this article. There is a strong relationship between these two phrases. When these two words are mentioned together, the word al-Zulumat always appears in the plural form while the word Al-Nur always appears in the Singular form, which shows that this Qur'anic phrase identifies the plural or singular form based on the source or origin of the word. In research on the lafadz al-Zulumat and al-Nur, the Munasabah verses approach which does not delve beyond the meaning of a word explanation is frequently utilized. As a result, the author's methodological strategy for conducting this field research comprises a semantic-linguistic analysis of both phrases. This literature study uses qualitative research methods, by collecting various data from books, journal articles and other relevant documents related to the semantic topic of the Al-Qur'an. The aim of this research is to examine the secrets contained in the words al-Zulumat which are often compared with the words al-Nur. The research conducted found that these two expressions combined signify the sequential emergence of direction as well as the process of creation. This article is important for exploring the linguistic and rhetorical special that exists in Al-Qur'an phrases, especially in the words al-Zulumat and Al-Nur.